2021
DOI: 10.3390/pharmaceutics13060774
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibody Stability in a Novel Protein-Free Serum Model

Abstract: Therapeutic proteins can degrade upon administration as they are subjected to a variety of stresses in human body compartments. In vivo degradation may cause undesirable pharmacokinetic/pharmacodynamic profiles. Pre-clinical in vitro models have gained scientific interest as they enable one to evaluate the in vivo stability of monoclonal antibodies (mAbs) and ultimately can improve patient safety. We used a novel approach by stripping serum of endogenous proteins, which interfere with analytical test methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Normal saline is isotonic and consists of 0.9% NaCl . However, once the sample containing mAb is administered in the body, it is exposed to various salts, pH of 7.4, and different small and large molecules. , Hence, to determine the aggregation of mAb samples with FeSO 4 ·7H 2 O and H 2 O 2 after administration in the body, stability was investigated in extracellular saline and more complex in vitro models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal saline is isotonic and consists of 0.9% NaCl . However, once the sample containing mAb is administered in the body, it is exposed to various salts, pH of 7.4, and different small and large molecules. , Hence, to determine the aggregation of mAb samples with FeSO 4 ·7H 2 O and H 2 O 2 after administration in the body, stability was investigated in extracellular saline and more complex in vitro models.…”
Section: Resultsmentioning
confidence: 99%
“…Once the formulation of therapeutic IgG is administered in the body, the excipients will get diluted in the body fluids and the mAb would be exposed to different chemicals. , However, physiological fluid such as serum has a pH of 7.4 maintained by the carbonate–bicarbonate buffer , and has various salts, proteins, and small and large molecules. , Hence, the aggregation of mAb was explored in extracellular saline having a physiological pH and different ions other than Na + , and it was found that the sample in the combined presence of H 2 O 2 and Fe 2+ resulted in rapid aggregation of mAb.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the guidance for sub-visible particles is not designed to de-risk protein aggregation in vivo or immunogenicity concerns, but rather to avoid the risk of capillary occlusion 27 . Pre-clinical in vitro models are increasingly employed to evaluate the protein stability post injection 28 , 29 , 30 . For instance, a novel protein-free serum in vitro setup revealed faster degradation profiles for two monoclonal antibodies (mabs) compared to accelerated stability studies 30 .…”
Section: Protein Aggregation In Parenteral Versus Inhaled Productsmentioning
confidence: 99%
“…Pre-clinical in vitro models are increasingly employed to evaluate the protein stability post injection 28 , 29 , 30 . For instance, a novel protein-free serum in vitro setup revealed faster degradation profiles for two monoclonal antibodies (mabs) compared to accelerated stability studies 30 . However, the guidance for particulate levels serves as a unified regulation across parenteral formulations to limit particles, including protein aggregates, in the final product.…”
Section: Protein Aggregation In Parenteral Versus Inhaled Productsmentioning
confidence: 99%
“…Alternatively, the assessment of IC formation using degraded biologics material from incubation in biomatrices like serum could be an attractive option. Due to their extended half-life, many biologics are known to experience modifications from being exposed to elevated temperatures and to serum components [46].…”
mentioning
confidence: 99%